Karakteristik Morfologi Galur-Galur Padi (Oryza sativa L.) Fungsional yang Ditanam pada Dataran Medium: Morphological Characterization of Functional Rice (Oryza sativa L.) Lines Planted in Medium Plains - Amilia Qurota A'yun; I Gusti Putu Muliarta Aryana; I Wayan Sudika (LPPM Universitas Mataram, 2023)
This research aims to determine the morphological characteristics of functional rice (Oryza sativa L.) lines grown in medium plains. The research was conducted in May – August 2022, in medium plain paddy fields with an altitude of 370 m above sea level to be precise in Tampak Siring Village, Batukliang District, Central Lombok. The method used was an experimental method with field trials. The design used was a randomized block design (RBD) with 13 treatments and 3 replications, resulting in 39 experimental units. The parameters observed include quantitative characters and qualitative characters. Observation of characters in rice plants was carried out in the vegetative phase, generative phase, maturation to harvest phase and post-harvest phase. Morphological character analysis was carried out using the scoring method based on the definition of the IBPGR-IRRI Rice Advisory Committee, Guidelines for Characterization and Evaluation of Rice Plants and Guidelines for Implementation of Uniqueness, Uniformity, and Stability Tests for Rice. Based on the research results, It can be concluded that functional rice (Oryza sativa L.) lines grown on medium plains have different morphological characteristics.